Spatio-temporal distribution, diversity and monitoring of fruit flies (Diptera, Tephritidae) in papaya orchards in the state of Espírito Santo, Brazil - Araujo, Mayara Ribeiro de (2021)
The search for information on the ecology of fruit flies of economic importance (Diptera, Tephritidae) in agricultural areas has grown in recent decades due to food biosecurity. Knowledge about the long-term monitoring of these tephritids in agricultural ecosystems and the influence of neighboring areas have been the subject of an investigation by several researchers. However, research that compiles this information in only one study is still scarce. A system of management of fruit flies implemented more than 20 years ago in papaya orchards in the state of Espírito Santo, the systems approach, provided the export of papaya to the United States. This scenario provides favorable opportunities to investigate behavioral aspects of fruit flies in space and time. In this sense, the objective of this research was to know the spatio- temporal distribution and the community structure of fruit flies in areas of papaya production in the state of Espírito Santo. We used a time series of 13 years of weekly monitoring of the fruit flies of different georeferenced points in papaya crops. The species survey was carried out using McPhail and Jackson traps, using 1 trap per hectare in the areas. The study was divided into three sections. In the first, mathematical functions, partitioning of the diversity, and spectral analysis were used to describe the species-area relationship and patterns of species richness and abundance over time, under the influence of the systems approach and different distances from an Atlantic Rainforest. Species richness and abundance were influenced by time and distance, partitioning of diversity indicated changes in richness values within ?-diversity and spectral analysis projected different peak trends. In the second section, regression and frequency distribution analyzes were used to characterize the aggregation existing patterns of three species of fruit flies economically important for Brazil, in three areas with different distances from the Atlantic Rainforest and in two periods of the systems approach. The results showed that areas near the Atlantic Rainforest and the period of impact of the systems approach on abundance provided greater aggregation of species. Finally, a probabilistic model of species co-occurrence was used to know the patterns of interactions existing between species, as well as an analysis of interaction strength, was applied, to know how strongly associated species are between itself, comparing the different scenarios under study. Only positive and random associations were observed, the largest number of species pairs formed was in orchards more distant from the Atlantic Rainforest and in the period of continuous implementation of the systems approach. The strength of interaction for the positive association has changed slightly between areas and over the years. In all sections, the results describe changes in the population patterns investigated due to the systems approach and the influence of the Atlantic Rainforest in the different delimited areas. The information generated in this study contributes to the knowledge about the ecology of fruit flies in Brazil and generates information that may contribute to the optimization management of these tephritids in a wide area perspective.